2016
DOI: 10.1371/journal.pone.0149136
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Ligation and Puncture Results in Long-Term Central Nervous System Myeloid Inflammation

Abstract: Survivors of sepsis often experience long-term cognitive and functional decline. Previous studies utilizing lipopolysaccharide injection and cecal ligation and puncture in rodent models of sepsis have demonstrated changes in depressive-like behavior and learning and memory after sepsis, as well as evidence of myeloid inflammation and cytokine expression in the brain, but the long-term course of neuroinflammation after sepsis remains unclear. Here, we utilize cecal ligation and puncture with greater than 80% su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 77 publications
7
63
1
2
Order By: Relevance
“…Prior to death, animals would develop high-amplitude convulsions followed by decerebrate posturing. This is consistent with studies which have demonstrated neurologic deficits, including seizure, and neuronal apoptosis in animals suffering from endotoxic shock (Sayyah et al, 2003; Singer et al, 2016; Song et al, 2014). Hypoglycemia is a common cause of seizure, but we found that blood glucose did not differ significantly between groups over time (Figure S2B).…”
Section: Resultssupporting
confidence: 92%
“…Prior to death, animals would develop high-amplitude convulsions followed by decerebrate posturing. This is consistent with studies which have demonstrated neurologic deficits, including seizure, and neuronal apoptosis in animals suffering from endotoxic shock (Sayyah et al, 2003; Singer et al, 2016; Song et al, 2014). Hypoglycemia is a common cause of seizure, but we found that blood glucose did not differ significantly between groups over time (Figure S2B).…”
Section: Resultssupporting
confidence: 92%
“…ImageJ (NIH, Bethesda, MD) was count microglia, and a fractal analysis plugin in ImageJ was used to determine microglial morphology [FracLac V. 2.5, (Karperien, Ahammer, & Jelinek, 2013)]. Microglial activation state is commonly assessed using number and morphological changes where cells shift from a resting ramified state with extended, branching processes, to an activated ameboid state with a larger cell body and retraction of processes (Kondo, Kohsaka, & Okabe, 2011;Singer et al, 2016;Weberpals et al, 2009). Fractal analysis is a sensitive and quantitative method to assess small changes in microglial shape using measures of pattern complexity and selfsimilarity (fractal dimension) as well as heterogeneity (lacunarity) (Karperien et al, 2013;Young & Morrison, 2018).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Thus, in its more advanced stages, the septic syndrome disturbs the body immune system, involving the inflammatory mechanisms and the clotting cascade . Furthermore, this inflammatory response can lead to impairment of the central nervous system (CNS), which can trigger severe behavioural and cognitive changes .…”
mentioning
confidence: 99%